Run-Time Compilation of Bytecode in Sensor Networks - Ellul, Joshua; Martinez, Kirk (2010 Fourth International Conference on Sensor Technologies and Applications, 2010)
Recent work on virtual machines for wireless sensor networks has demonstrated the benefits of using a Java programming paradigm for resource constrained sensor networks. Results have shown that a virtual machine approach greatly suffers from interpretation overheads. In this paper, we present run-time compilation of bytecode in wireless sensor networks which leverages from both a compact platform independent bytecode program representation as well as a native execution platform for efficient execution of code. Our results show that run-time compilation provides a substantial decrease in execution overheads when compared with an interpreter.